World Food Prize Laureate 2009 shares his optimism with ILRI and BecA about the Future of African Agriculture - International Livestock Research Institute (International Livestock Research Institute, 2009)
On December 11 2009, the World Food Prize Laureate 2009, Prof. Gebisa Ejeta, visits the International Livestock Research Institute (ILRI) and Biosciences Eastern and Central Africa (BecA) in Nairobi, Kenya (Eastern Africa). He expresses great optimism about African Agriculture saying that Africa is ready for positive change; and both Africa’s leadership and external governments are committed to the continent’s improvement. He finally challenges the continent to prove itself since the timing is right. At the same time, the director of the BecA Hub, Dr. Segenet Kelemu, explains how BecA can deliver for better African agriculture. She says that her organization can deliver by strengthening capacity in Africa through providing new technology and cutting edge science; and applying these to solve the continent’s problems. She also adds that BecA provides hope and optimism that hi-tech science can be done in the continent.